2002
DOI: 10.1080/0265203021000011214
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of aflatoxins B 1, B 2, G 1 and G 2 in some Brazilian pet foods

Abstract: The presence of cereals and grains in the formulation of pet foods suggests the need to control aflatoxin contamination in these foods. The objective of the study was to analyse domestic pet food to determine the occurrence of aflatoxins as well as their risk to animal health. One hundred food samples (45 for dogs, 25 for cats, 30 for birds) were collected at random from pet shops in Alfenas city, south-east Brazil. Thin-layer chromatography was used for separation, identification and quantification of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 5 publications
3
27
2
2
Order By: Relevance
“…However, aflatoxin-contaminated pet feeds have been found in surveys conducted in the states of Minas Gerais [20] and Santa Catarina [9]. Pleadin et al [21] confirmed the corn as the main source of aflatoxin contamination in feeds in Croatia, where high incidences of aflatoxins at levels ranging from 1.1 to 2,072 µg/kg were found in corn samples from different farms and feed factories.…”
Section: Simultaneous Occurrence Of Aflatoxins and Fumonisins In Cornmentioning
confidence: 87%
“…However, aflatoxin-contaminated pet feeds have been found in surveys conducted in the states of Minas Gerais [20] and Santa Catarina [9]. Pleadin et al [21] confirmed the corn as the main source of aflatoxin contamination in feeds in Croatia, where high incidences of aflatoxins at levels ranging from 1.1 to 2,072 µg/kg were found in corn samples from different farms and feed factories.…”
Section: Simultaneous Occurrence Of Aflatoxins and Fumonisins In Cornmentioning
confidence: 87%
“…Feeds for dogs and cats contain small amounts of aflatoxins. Almost all the feed samples that these mycotoxins were found in, contained less than 20 µg AFB 1 /kg [6]. Such a low level of aflatoxins in the feed does not cause any symptoms of acute poisoning.…”
Section: Aflatoxinsmentioning
confidence: 98%
“…In animals the clinical symptoms of ergotism are as follows: dry gangrenes, ulcerations, necroses, blindness, convulsions, hypersensitivity and ataxia, and lactation inhibition [6]. A number of ergot alkaloids cause contractions of smooth muscles (e.g.…”
Section: Ergot Alkaloidsmentioning
confidence: 99%
“…O termo aflatoxina designa um grupo de micotoxinas, cujos principais tipos são aflatoxina B1, mais tóxica e mais abundante nos substratos; aflatoxinas B2, G1, G2, M1 e M2, sendo as duas últimas produtos metabólitos de B1 e B2 (Puschner 2002, CAST 2003. No Brasil e em outros paí-ses, níveis significativos de aflatoxinas têm sido detectados em amostras de ração comercial para cães (Maia & Siqueira 2002, Boermans & Leung 2007. Seus efeitos nos animais variam de acordo com a dose, o tempo de exposição, a espé-cie, a raça e o estado nutricional, podendo ser letais quando as aflatoxinas são ingeridas em grandes quantidades.…”
Section: Introductionunclassified